(3UahI GdRHO aj Gdabg GdTGaYjs - (3GHf QSdGf, CMeO Hf MSjf Hf MSf, J (B844 (3g`s ((3eOQSI GdNjGWjf (B( (3eOQSI YHO GdbGOQ CafOj GdNWjH (B)s)
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddEdg Pj GdLdGd (B= (3hTGQY GdMQGe hGdMdGdj (B( (3cPG (B) (3aj GdCUd , Ke UdGI Gddg eY SdGej (B= (3Ydi GdfHj GdeUWai GdJgGej (B- (3eMeO GdgGOj ef GdVdGd (B= (3hCaVd GdUMH NjQ Bds
(3BNQgG (B:s
(3hGdMeO ddg Ydi GdceGd (B= (3SGFd Jhajb dMSf MGd (B- (3Ke GdUdGI hGdSdGe CHOG (B= (3Ydi GdfHj GdgGTej CMeOG (B- (3hGdBd hGdUMH hef dge baG (B= (3hMSHfG Gddg JYGdi hcais
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdHOQ GdWGdY (B1/36s
(3GdVhA GddGeY (B1/ 282s
(3TPQGJ GdPgH (B7 / 248s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3Gdabg GdTGaYjs